INFORMALITY CONFLICT IN FORMALITY AT PUBLIC SPACE IN THE FORM OF OPEN SPACE, PEDESTRIAN AND STREET (A CASE STUDY: PANAKKUKANG AREA, MAKASSAR) - Sherly Asriany (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2012)
The problem of use and interest at public space is very obvious in several areas or objects causing the conflict. The conflict arises due to the difference of use and difference of interest which also affects the level of policy making of the municipal government concerned. In the field of architecture and urban planning, problems in the use of ‘public space’ need serious attention from all of us because the use of public space involves many parties which have interest in it. In case of Panakkukang area, it has become a town problem hard to solve accurately because there are many people and a lot of interests involve in it. The problem of planning and architecture cannot solve the town problems arises. The use of open space (parks/yards/parking lot), pedestrian rood and motor vehicle is mixed up, disorder and causes many conflict. It is not only about mixed up use of public spaces, but the users and other parties have interest in socio-economic, socio-politic and socio-culturally. The result of the conflict in the use of public space has unavoidable effects such as disorder, insecurity, inconvenience, informality conflict in formality use of ‘space and conflict of interest’ from related parties. In this writing, there is a need to look at, observe and analyze the aspect of informality conflict in formality use and conflict of interest of public space comprising three kinds of spaces, those are: (a) open space (park, yard, and parking lot), (b) pedestrian road, and (c) vehicle road. And at this time discourse of informality in formality of public space becomes an important issue that much be put in the appropriate position. In observing and studying the problems mentioned above, the writer chose the case of Panakkukang area in Makassar.